Risk factors for developing capsular contracture in women after breast implant surgery: A systematic review of the literature. Issue 9 (September 2018) - Bachour, Yara; Bargon, Claudia A.; de Blok, Christel J.M.; Ket, Johannes C.F.; Ritt, Marco J.P.F.; Niessen, Frank B.
Summary: Background: Capsular contracture is the most frequent complication in breast augmentation or reconstruction with breast implants. The exact mechanism for this complication is not completely understood. Yet, it is most likely to be a multifactorial condition. Several patient-, surgery-, and implant-specific risk factors have been related to cause capsular contracture. This review aims to provide a clear overview of all risk factors for capsular contracture. Methods: A systematic literature review was performed focusing on patient-, surgery-, and/or implant-related factors related to capsular contracture in breast implants. PubMed, Embase, and Wiley/Cochrane Library databases were searched for relevant articles published from inception up to October 20, 2016. The included studies were assessed for the following main variables: study characteristics, patient characteristics, indication for surgery, type of surgery, implant characteristics, and other characteristics. Results: Data on the risk factors for the development of capsular contracture were retrieved from 40 studies. A presumptive increased risk in the development of capsular contracture is shown for the following variables: longer duration of follow-up, breast reconstructive surgery in patients with a history of breast cancer, subglandular implant placement, postoperative hematoma, and a textured implant surface. There is little, weak, or no evidence for the association of other factors with capsular contracture. This review also shows a large heterogeneity between studies and within the definition of capsular contracture. Conclusion: This review provides an overview of the relationship between patient-, surgery-, and implant-specific risk factors in the development of capsular contracture.